Sejarah Kodifikasi Mushaf Utsmani: Kritik atas Orientalis & Liberal - Moh Isom Mudin (Tasfiyah: Jurnal Pemikiran Islam, 2017)
This paper attempts to discuss about orientalis and liberal critics to the Mushaf Usmani or Mushaf al-Imam. This study begins with their claim to criticize the authenticity of the Mushaf. With historical analysis, they found some problems. That is, there is a political issue quraisy in codification, intervention of the tribe of Quraisy in the formation of a commission that had implications for the election of the written Quraisy dialec, there are many friends of Nabi (sahabah) who disagree, even reject the Uthmanic manuscripts, even with missing verses and additional verses. Because of this, the Uthmanic manuscripts according to them were not authentic, and they filed the Shana manuscripts as it’s successor. Thus by using the same approach, The reasearcher found that the issues they raised were incorrect. The approach that they use to the Qur’an is not appropriate, because the approach is specific to the Bible. The allegations of intervention and Quraisy hegemony behind the codification are not scientifically prove.